Tarbiyah in the Digital Age: An Islamic Behavioral Framework for Reducing the Duration of Gadget Use in Preschoolers - Abdillah, Husni; Pangastuti, Ratna; Erfansyah, Nasrul Fuad (International Journal of Islamic Thought and Humanities, 2025)
This study addresses the growing issue of excessive gadget use by framing behavior modification within the principles of Islamic child-rearing (Tarbiyah al-Awlad). The primary aim was to reduce gadget dependency and screaming behavior in a preschooler by applying an intervention model that is spiritually meaningful for Muslim families. This research employed a single-subject (AB design) experimental approach with a 4-year-old male participant. The intervention was adapted to align with Islamic values: the token economy was transformed into a "Good Deed Star" (Bintang Kebaikan) system to reinforce patience (sabr), and time-out was reframed as a "Reflection Time" (Waktu Muhasabah) to encourage self-control. Data, collected via parental observation logs, showed a significant reduction in daily gadget use from an average of 108.6 minutes during baseline to 47.8 minutes during intervention. The conclusion is that integrating behavioral techniques within an Islamic Tarbiyah framework is highly effective. This study implies that such a model not only modifies behavior but also provides parents with a practical, faith-aligned tool for cultivating positive character (akhlak) in the digital age.